2015
DOI: 10.1016/j.biombioe.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Can productivity and post-pruning growth of Jatropha curcas in silvopastoral systems be regulated by manipulating tree spacing/arrangement without changing tree density?

Abstract: The potential of tree spacing/arrangement to alleviate effects of interspecific competition of hedgerow intercropping systems on productivity and response to pruning of Jatropha curcas was investigated using a Jatropha curcas -Pennisetum clandestinum (kikuyu) silvopastoral system at Ukulinga (KwaZulu Natal, South Africa). Treatments were differentiated by presence/absence of kikuyu and arrangement/spacing of Jatropha trees (one, two and three tree hedgerows on either side of the alley) and had the same tree de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…Jatropha and kikuyu are mostly dormant during extended dry periods and active during the rest of the year leaving no room for temporal complementarity between them. Ghezehei et al (2015) reported significant stem growth in the treatments of the current study, which was in agreement with a study by Huth et al (2010) that tree roots can explore intercropping zone for water before and during growing seasons. Taking into consideration total productivity (trees and grass) and total ET (Table 1), DR in our study was better tree arrangement than SR.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Jatropha and kikuyu are mostly dormant during extended dry periods and active during the rest of the year leaving no room for temporal complementarity between them. Ghezehei et al (2015) reported significant stem growth in the treatments of the current study, which was in agreement with a study by Huth et al (2010) that tree roots can explore intercropping zone for water before and during growing seasons. Taking into consideration total productivity (trees and grass) and total ET (Table 1), DR in our study was better tree arrangement than SR.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, tree arrangement without changing density had no consistent effects on tree growth and yield (Ghezehei et al 2015), and tree allometric relationships were not affected by interspecific competition or tree arrangements (Ghezehei et al 2009). High grass growth coincided with high rainfall periods, and grass yield consistently increased with increasing distance from tree rows, which was in agreement with previous studies (González-Hernández and Rozados-Lorenzo 2008; Huth et al 2010).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Research by Ghezehei et al (2015) showed yearly variations of HI from 0.5 % to 2.5 % in three year old jatropha-kikuyu grass silvopastoral, observed over a two year period. Our results are within these parameters.…”
Section: Above and Belowground Biomass And Harvest Indexmentioning
confidence: 99%
“…Information on biomass partitioning in the reproductive part as fruit/seed yield or HI is limited, with exception of Ghezehei et al (2015), direct (economic) yield is the most common measure used. The reason for this is likely due to the fact that jatropha is a perennial and yield may not be harvested until several years after planting, which unlike HI for annuals is easily determined on seasonal or annual basis.…”
Section: Above and Belowground Biomass And Harvest Indexmentioning
confidence: 99%